Looking for what’s native: Unknowns, confirmation biases and other reflections on understanding the culture of ancient and colonial Andean peoples - Ramírez, Susan (2024)
Based on examples and personal experiences in reading and analyzing written sources, this note demonstrates the heuristic and methodological issues that the ethnohistorian must keep in mind when carrying out research on the ancient and colonial Andean world. In particular, it highlights the complex unknowns that may arise when reviewing documents, the researcher’s own confirmation biases, and the inescapable need for an interdisciplinary perspective.